The implementation of lean manufacturing in Malaysian automotive industry - S., Ahmad Fakhri; Jahare, Muhammad Hafiz; Abd. Rahman, Mohamed (Trans Tech Publications, Switzerland, 2012)
The study was conducted to investigate the level of implementation of lean manufacturing (LM) in Malaysian automotive industry. A number of survey methodologies were utilized to ensure reliability of the results of this study. Thirteen areas have been identified as typical workplaces implementing lean manufacturing. The study also investigated the benefits gained and obstacles faced by manufacturers in implementing the system. The frequency and tendency of applying lean tools in manufacturing environment have also been ranked.